Towards a Sustainable Energy Planning Strategy: The Utilisation of Floor Area Ratio for Residential Community Planning and Design in China - Cheshmehzangi, Ali; Dawodu, Ayotunde (Frontiers in Sustainable Cities, 2021)
Floor Area Ratio, commonly known as FAR, is a major primary planning metric in urbanism. It is interpreted commonly known as the ratio of accumulated built floor areas against the size of a site/plot. In recent years, China’s rapid urban development has resulted in a substantial increase in FAR, particularly in residential areas. A notable shift from low-rise row housing typology to a more common high-rise residential unit is certainly a key factor behind the increase of energy use in many Chinese cities; . This factor highlightinghighlights the need for a sustainable energy planning strategy at the community level. As a novelty, this study reflects on the FAR changes in the context of China, and evaluates the impacts on energy use at the community scale. This study tests four models of FARs FAR models ofat 1.0, 2.5, 3.0, and 4.0 and provides a comparisonprovides a computational modelling analysis, with a comparison analysis. FAR models of 1.0 and 4.0 are typical models of low-rise and mid-to-high rise, respectively. Findings suggest FAR 4.0 as the least efficient for energy planning while FAR 1.0 is the least economically viable model. The results support policy development on FAR monitory, and paradigm shifts for future urban development models, particularly for the small to medium-scale residential compounds in cities.